1996
DOI: 10.1177/016224399602100103
|View full text |Cite
|
Sign up to set email alerts
|

Child Care, Research Collaboration, and Gender Differences in Scientific Productivity

Abstract: Large differences in scientific productivity between male and female researchers have not yet been explained satisfactorily. This study finds that child care and lack of research collaboration are the two factors that cause significant gender differences in scientific publishing. Women with young children and women who do not collaborate in research with other scientists are clearly less productive than both their male and female colleagues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
152
3
21

Year Published

1998
1998
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(186 citation statements)
references
References 17 publications
(14 reference statements)
10
152
3
21
Order By: Relevance
“…Female researchers are less likely to have publications and citations in Web of Science, and those who are represented in the database have a lower publication and citation count than their male colleagues. The poorer performance of female professors in bibliometric analyses versus their male colleagues corroborates existing findings (Aaltojärvi et al 2008, Kyvik 1996, Puuska 2010, Rauber and Ursprung 2008 for other countries and other fields. However, gender differences as regards citation count, citation count per publication, and h-index (Web of Science) are attributable at least in part to the effect of isolated statistical outliers and lose (some) statistical significance when these are controlled for.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…Female researchers are less likely to have publications and citations in Web of Science, and those who are represented in the database have a lower publication and citation count than their male colleagues. The poorer performance of female professors in bibliometric analyses versus their male colleagues corroborates existing findings (Aaltojärvi et al 2008, Kyvik 1996, Puuska 2010, Rauber and Ursprung 2008 for other countries and other fields. However, gender differences as regards citation count, citation count per publication, and h-index (Web of Science) are attributable at least in part to the effect of isolated statistical outliers and lose (some) statistical significance when these are controlled for.…”
supporting
confidence: 87%
“…Gender: Various studies show that the publishing output of female researchers is lower than that of their male counterparts (Aaltojärvi et al 2008, Kyvik 1996, Larivière et al 2011, Puuska 2010, Rauber and Ursprung 2008, Smeby and Try 2005. In contrast, findings indicating positive effects of female gender on research output are rare (De Witte and Rogge 2010).…”
mentioning
confidence: 99%
“…1,2 In this paper, an attempt is made to identify possible demographic and academic factors that help to improve the research output of academics at the University of KwaZulu-Natal (UKZN). Similar studies have been conducted, mainly on US data (for example Xie and Shauman 3 , Aksnes et al 4 and Kyvik and Teigen 5 ), in which it was found that for almost every age group in their respective data sets, men publish more than women. Barjak 6 , Gonzalez-Brambila and Veloso 7 and Kyvik 8 have found that research productivity tends to increase with age, reaching a peak before tapering off towards retirement.…”
Section: Introductionsupporting
confidence: 60%
“…The same observation and its possible explanations have been studied more extensively in previous studies, e.g. by Kyvik & Teigen (1996) Scientific Productivity". That study, however, was based on a survey and interviews with relatively few researchers.…”
Section: Limitations and Potentials Of Current Research Information Smentioning
confidence: 56%